Regionally clustered ABCC8 polymorphisms in a prospective cohort predict cerebral oedema and outcome in severe traumatic brain injury. Issue 11 (19th April 2018) - Jha, Ruchira Menka; Koleck, Theresa A; Puccio, Ava M; Okonkwo, David O; Park, Seo-Young; Zusman, Benjamin E; Clark, Robert S B; Shutter, Lori A; Wallisch, Jessica S; Empey, Philip E; Kochanek, Patrick M; Conley, Yvette P
Abstract : Objective: ABCC8 encodes sulfonylurea receptor 1, a key regulatory protein of cerebral oedema in many neurological disorders including traumatic brain injury (TBI). Sulfonylurea-receptor-1 inhibition has been promising in ameliorating cerebral oedema in clinical trials. We evaluated whether ABCC8 tag single-nucleotide polymorphisms predicted oedema and outcome in TBI. Methods: DNA was extracted from 485 prospectively enrolled patients with severe TBI. 410 were analysed after quality control. ABCC8 tag single-nucleotide polymorphisms (SNPs) were identified (Hapmap, r 2 >0.8, minor-allele frequency >0.20) and sequenced (iPlex-Gold, MassArray). Outcomes included radiographic oedema, intracranial pressure (ICP) and 3-month Glasgow Outcome Scale (GOS) score. Proxy SNPs, spatial modelling, amino acid topology and functional predictions were determined using established software programs. Results: Wild-type rs7105832 and rs2237982 alleles and genotypes were associated with lower average ICP (β=−2.91, p=0.001; β=−2.28, p=0.003) and decreased radiographic oedema (OR 0.42, p=0.012; OR 0.52, p=0.017). Wild-type rs2237982 also increased favourable 3-month GOS (OR 2.45, p=0.006); this was partially mediated by oedema (p=0.03). Different polymorphisms predicted 3-month outcome: variant rs11024286 increased (OR 1.84, p=0.006) and wild-type rs4148622 decreased (OR 0.40, p=0.01) the odds of favourable outcome. Significant tag and concordant proxy SNPs regionally span introns/exons 2–15 of the 39-exon gene. Conclusions: This study identifies four ABCC8 tag SNPs associated with cerebral oedema and/or outcome in TBI, tagging a region including 33 polymorphisms. In polymorphisms predictive of oedema, variant alleles/genotypes confer increased risk. Different variant polymorphisms were associated with favourable outcome, potentially suggesting distinct mechanisms. Significant polymorphisms spatially clustered flanking exons encoding the sulfonylurea receptor site and transmembrane domain 0/loop 0 (juxtaposing the channel pore/binding site). This, if validated, may help build a foundation for developing future strategies that may guide individualised care, treatment response, prognosis and patient selection for clinical trials.